The Use of Transition Signals in University Students’ Community Service Report - Utami, Ni Putu Cahyani Putri; Mahendra, Made Wahyu (Yavana Bhasha : Journal of English Language Education, 2021)
Transition signals are the essential elements to achieve a well-structured text. The ideas in the text need to connect to each other. It will be difficult for the reader to understand the sequence if the ideas are simply just exposed by the writer without being related to each other. Students’ competency and ability in English academic writing overviewed from their competence in constructing sentences. Therefore, this research aimed to find out the use of transition signals and their accuracy in students’ community service report. The research used a descriptive quantitative method. The data were taken from students’ community service report written by the seventh semester English literature students of Foreign Languages Study Program of Universitas Mahasaraswati Denpasar. The finding of this research showed that the total number of transition signals used by the students in their community service report were 303 and classified into eight types of transition signals. Transition signals to introduce sequence and logically order ideas was mostly used and transition signals to emphasize ideas was least used by the students. From the whole types of transition signals, the average usage accuracy was above 60%.